Social Media Use and Mental Health in Young Adults of Greece: A Cross-Sectional Study - Epameinondas Leimonis; Katerina Koutra (Clinical Psychology in Europe, 2022)
[Background] Social media use has vastly increased during the past few years, especially among young adults. Studies examining the relationship of social media use with mental health have yielded mixed findings. Additionally, such studies are extremely limited in Greece. The present study aimed to investigate the association between social media use, depressive symptoms and self-esteem among Greek young adults. [Method] A total of 654 individuals (50.5% male) aged 18-30 years (Μ = 23.62, SD = 2.71) completed self-reported questionnaires regarding social media use, depressive symptoms and self-esteem. [Results] Increased daily use of YouTube (more than five hours) showed a significant association with higher depressive symptomatology, b = 2.99, 95% CI [.78, 5.20], p = .008, while daily use of Facebook between two and five hours was related to significantly higher self-esteem, b = 1.61, 95% CI [.78, 2.44], p < .001, after adjusting for participants’ gender, age, educational level and employment status. The association of increased daily use of YouTube with depressive symptoms was more pronounced in males than in females. Moreover, self-reported active use of Facebook and Instagram were linked with significantly lower depressive symptoms and higher self-esteem compared to passive involvement. [Conclusion] The results suggest that social media use is closely related to self-esteem and depressive symptomatology in young adults. These findings may contribute to a deeper clinical understanding of the association between electronic social networking and mental health.